Effect of Organically-Modified Titania Nanoparticles on the Performance of Poly(3-hexythiophene): PCBM Bulk Heterojunction Solar Cells. Issue 1668 (29th August 2014) - Park, Sun Young; Ahn, Haeng Hee; Yoon, Jiyeon; Kim, Sang Yong; Hwang, Bora; Yoon, Tae Gi; Kwon, Yong Ku
ABSTRACT: The modified TiO2 nanoparticles were incorporated into the Bulk heterojunction system of P3HT:PCBM to improve the performance of P3HT:PCBM bulk heterojunction organic solar cells. The organically-modified TiO2 nanoparticle compounds were synthesized in aqueous media at room temperature. These TiO2 compounds in various solution concentrations were deposited on the top of the P3HT:PCBM active layer by spin coating. The performance of organic solar cells was carefully investigated in the respect of the scattering and the localized surface plasmon resonance (LSPR) that couple strongly to the incident light. In addition to the device, P3HT:PCBM solar cells with the use of the TiO2 nanoparticles, enhanced Fill Factor (FF) due mainly to improved shunt resistance (Rsh). The TiO2 plays a critical role in improving the interface between P3HT:PCBM active layer and Al electrode.